2016
DOI: 10.1177/1756285616677004
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenazine in treatment of hyperkinetic movement disorders: an observational study

Abstract: Background: Tetrabenazine (TBZ) is commonly used in hyperkinetic movement disorders. In this retrospective study, we aimed to assess the TBZ effectiveness and adverse events (AEs) in Huntington disease (HD), vascular chorea, tics, dystonia, tardive oromandibular (OM) dyskinesia and other tardive syndromes (TS). Methods: Qualitative analysis of clinical response was used to estimate TBZ effectiveness. TBZ-associated AE frequency and subsequent discontinuation rate were used to estimate tolerability; the tolerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Because this open-label study was only presented orally in a platform session at the 2016 American Academy of Neurology (AAN) Annual Meeting, information about the methods and results were limited. Nine studies were identified for tetrabenazine: one double-blind, crossover study [31]; and eight open-label studies, which included two case series [32,33], three long-term studies [34][35][36] and three retrospective chart reviews [37][38][39]. Full-text review resulted in the exclusion of one open-label case series [32] because only four of the 14 TD patients were treated with tetrabenazine.…”
Section: Search Strategy Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because this open-label study was only presented orally in a platform session at the 2016 American Academy of Neurology (AAN) Annual Meeting, information about the methods and results were limited. Nine studies were identified for tetrabenazine: one double-blind, crossover study [31]; and eight open-label studies, which included two case series [32,33], three long-term studies [34][35][36] and three retrospective chart reviews [37][38][39]. Full-text review resulted in the exclusion of one open-label case series [32] because only four of the 14 TD patients were treated with tetrabenazine.…”
Section: Search Strategy Resultsmentioning
confidence: 99%
“…The tetrabenazine studies also included retrospective chart reviews by Paleacu et al [37] and Miguel et al [39]. Both studies examined the effects of tetrabenazine on TD and other movement disorders in patients who did not respond to other medications.…”
Section: Review Of Tetrabenazine Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Klozapin ilginç şekilde mevcut geç diskinezi tedavisinde potansiyel etkiye sahiptir. 29,30 Tetrabenazin ve rezerpinin geç diskinezi ve geç distoni için en etkili ilaçlar olduğu gösterilmiştir. 29,31 Klonazepam ile naltrekson kombinasyonunun, muhtemelen beyin GABA ve bazal ganglionlar ensefalinerjik nöronlar üzerinde etkileşimin bir sonucu olarak, geç diskinezi iyileştirmede etkili olduğu bulunmuştur.…”
Section: Geç Di̇ski̇nezi̇unclassified